Pseudomonas syringae naturally lacking the canonical type III secretion system are ubiquitous in nonagricultural habitats, are phylogenetically diverse and can be pathogenic - Diallo, Moudjahidou Demba (Nature Publishing Group, 2012)
The type III secretion system (T3SS) is an important virulence factor of pathogenic bacteria, but the natural occurrence of variants of bacterial plant pathogens with deficiencies in their T3SS raises questions about the significance of the T3SS for fitness. Previous work on T3SS-deficient plant pathogenic bacteria has focused on strains from plants or plant debris. Here we have characterized T3SS-deficient strains of Pseudomonas syringae from plant and nonplant substrates in pristine nonagricultural contexts, many of which represent recently described clades not yet found associated with crop plants. Strains incapable of inducing a hypersensitive reaction (HR(−)) in tobacco were detected in 65% of 126 samples from headwaters of rivers (mountain creeks and lakes), snowpack, epilithic biofilms, wild plants and leaf litter and constituted 2 to 100% of the P. syringae population associated with each sample. All HR(−) strains lacked at least one gene in the canonical hrp/hrc locus or the associated conserved effector locus, but most lacked all six of the genes tested (hrcC, hrpL, hrpK1, avrE1 and hrpW1) and represented several disparate phylogenetic clades. Although most HR(−) strains were incapable of causing symptoms on cantaloupe seedlings as expected, strains in the recently described TA-002 clade caused severe symptoms in spite of the absence of any of the six conserved genes of the canonical T3SS according to PCR and Southern blot assays. The phylogenetic context of the T3SS variants we observed provides insight into the evolutionary history of P. syringae as a pathogen and as an environmental saprophyte.